1995
DOI: 10.3354/meps119139
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of the velvet swimming crab Necora puber in mussel raft areas of the Ría de Arousa (Galicia, NW Spain)

Abstract: The feeding ecology of the velvet swimming crab Necora puber (Decapoda: Portunidae) in 3 mussel raft culture areas of the Ria de Arousa (Galicia. NW Spain) was studied through the analysis of stomach contents. The dominant prey was Pisidia longicornis (50 to 81 % of the diet in the different areas), a small epifaunal anomuran crab that inhabits culture ropes. Other important food components were brachyuran crabs, the mussel Mytilus galloprovincial~s and other bivalves, gastropods, egg cases of the gastropod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 30 publications
1
36
0
1
Order By: Relevance
“…compared to adjacent soft bottom habitats). The existence of a trophic mechanism is also supported by the studies by Freire et al (1990) and Freire & González-Gurriarán (1995), who showed that crabs in mussel culture areas increase the proportion of mussels in their diets relative to that of crabs in areas outside of mussel farms. A trophic mechanism also supports observations of variation in the distribution of macrofauna within farms.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…compared to adjacent soft bottom habitats). The existence of a trophic mechanism is also supported by the studies by Freire et al (1990) and Freire & González-Gurriarán (1995), who showed that crabs in mussel culture areas increase the proportion of mussels in their diets relative to that of crabs in areas outside of mussel farms. A trophic mechanism also supports observations of variation in the distribution of macrofauna within farms.…”
Section: Introductionsupporting
confidence: 61%
“…Mussels are among the main prey items of rock crabs in coastal areas and in the general study area (Drummond-Davis et al 1982, Hudon & Lamarche 1989. Romero et al (1982) observed a greater abundance of various crab species in areas with mussel rafts than in areas without them in the Ría de Arousa, Spain, and stomach content analysis of crabs in the same region showed crab diets shift to include more mussels in farm areas (Freire et al 1990, Freire & González-Gurriarán 1995. Likewise, mussels are the preferred prey of many starfish (Penney & Griffiths 1984, Gaymer et al 2001, and aggregations of starfish have often been noted with fallen mussels at mussel farm sites (Olaso Toca 1982, D'Amours et al 2008, Wilding & Nickell 2013, suggesting that they are attracted to mussel farms for the abundant prey they offer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the crab Necora puber shows increased preference for fish and decapods with growth and reduces the predation on non-decapod crustaceans and plants (Freire and González-Gurriarán, 1995). In general, an increase in the predator size means that the prey size will increase (Dall et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…González-Gurriarán (1986) and Freire & González-Gurriarán (1995) showed that mussel rafts constituted an important source of food for crabs. Likewise, Romero et al (1982) showed that increased crab density was associated with the abundance of food from sessile epifaunal species and biodeposition.…”
Section: Discussionmentioning
confidence: 99%